Comparative Performance of Imported and Home Bred Holstein Friesian Cows: Corrected and Average Daily Milk Production. - Kharoofa, A.D.S.; Ahmed, M-K. A.; Salhab, S.A.; Zaied, A.A. (Al-Mukhtar Journal of Sciences, 1997)
A. total of 3013 production records from Ghot Al-Sultan dairy cattle unit were used. The records were made by information collected from a number of imported cows and their locally born daughters. The differences between these two groups in 3x305, 2x305 milk yield and average daily milk yield were studied. in addition som general eneral environmental factors were studied.. Results showed the presence of significant (P<0.01) differences between the imported and local groups. in the first two lactations for all three traits. The effect of calving years on the three traits were significant (P<0.01) in the first lactation only for the imported groud group and in all three lactations in the local group. Season effects on 3x305 and 2x305 production were significant (P<0.01) in the first two lactations They were also highly significant (P<0.01) on average daily production in the first lactation and significant (P<0.05) in the second lactation. The regressions of three traits on age at calving were not significant except for 2x305 and average daily daily production in the first lactation only. The linear, quadratic and cubic regressions on length of lactation were significant in all three lactations.